Effects of Middle School Teachers' Praise-to-Reprimand Ratios on Students' Classroom Behavior. (January 2023) - Caldarella, Paul; Larsen, Ross A. A.; Williams, Leslie; Wills, Howard P.
Middle school teachers frequently struggle with positively managing student behavior. However, praise-to-reprimand ratios (PRRs) have received little research attention. PRRs studied in elementary school have been positively associated with improvements in on-task and prosocial behavior, but limited research has been conducted on optimal PRRs in middle schools. We conducted this study in the context of a randomized control trial of Class-wide Function-related Intervention Teams Middle School (CW-FIT MS) to isolate the effects of one of the main components of the intervention, PRR. After controlling for the intervention, we examined the effects of PRRs in 28 U.S. middle school classrooms on (a) class-wide on-task behavior, (b) on-task behavior of students at risk for emotional and behavioral disorders (EBD), and (c) disruptive behavior of students at risk for EBD. Multivariate regressions revealed a statistically significant linear relationship between middle school PRRs and the variables of interest: As PRRs increased, on-task behavior of the entire class improved, on-task behavior and grades of students at risk for EBD increased, and disruptive behavior of students at risk for EBD decreased. We discuss the implications of our findings and suggest areas for future research.